2017
DOI: 10.3382/ps/pex155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rearing systems on laying performance, egg quality, and serum biochemistry of Xianju chickens in summer

Abstract: The objective of this study was to compare the laying performance, egg quality, and serum biochemistry of hens maintained in conventional cage rearing system (CRS), flat net-rearing system (NRS), and free range system (FRS) under summer conditions. Indigenous Xianju chickens (n = 540) were randomly allocated into cages or pens of rearing system groups, within each system there were 5 replicates with 36 hens in each replicate. The experiment lasted between 21 and 29 wk of age. Hen-day egg production (P = 0.00) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Küçükyılmaz et al (2012) reported no effect of the housing system on egg yolk cholesterol content. Similarly, Dong et al (2017) did not demonstrate differences in cholesterol content in the yolk of eggs from both free-range with or without outdoor access. In our study, the differences in egg yolk cholesterol levels between the studied breeds were not significant (Table 4.).…”
Section: Resultsmentioning
confidence: 73%
“…Küçükyılmaz et al (2012) reported no effect of the housing system on egg yolk cholesterol content. Similarly, Dong et al (2017) did not demonstrate differences in cholesterol content in the yolk of eggs from both free-range with or without outdoor access. In our study, the differences in egg yolk cholesterol levels between the studied breeds were not significant (Table 4.).…”
Section: Resultsmentioning
confidence: 73%
“…This reduction may be attributed to the increased physical activity in ducks allowed to access a yard and a swimming pool. Similarly, Dong et al [41] reported that a reduction in serum triacylglycerol and cholesterol of Xianju chickens was due to yard rearing.…”
Section: Resultsmentioning
confidence: 92%
“…Guni et al (2021a) which also showed lower performance of onfarm than on-station management in most egg production traits. Similarly, Champati et al(2020) reported heavier eggs for intensively reared chickens than for semi-intensive whileDong et al (2017) andKucukyılmaz et al (2012) also observed variation in egg weight for different rearing systems. In contrast to the present ndings,Patel et al (2018) andSokołowicz et al (2018) did not nd signi cant differences in egg weight between deep litter and other rearing systems.…”
mentioning
confidence: 95%